Hubungan Tingkat Pengetahuan Dan Sikap Mahasiswa Terhadap Kejadian Acne Vulgaris - Muhamad Aldo Putra; Helmice Afriyeni; Dwisari Dillasamola (CV. ITTC INDONESIA, 2023)
So far, there are still many people who prioritize and assume that physical appearance is the key in interacting both directly and interacting on social media. In the campus environment, students have very wide interactions and are concerned with appearance to bind self-confidence, therefore the importance of students' knowledge and attitudes towards the incidence of acne vulgaris. This study aims to determine whether or not there is a relationship between the level of knowledge and attitudes of students towards acne vulgaris. This study used descriptive analytic method with cross sectional design and the sampling used random sampling method and data analysis using chi-square. The results obtained were in the knowledge test of Dharma Andalas University Padang students the majority were in the good category (82.78%) and the results on the attitude test were the majority in the sufficient category (65.57%). In the results of the chi-square test analyzing the relationship between knowledge and attitudes towards the incidence of acne vulgaris, the p value = 0.039 (p < 0.05) and p = 0.813 (p> 0.05) and in the analysis of knowledge and attitude, p = 0.796 ( p>0.05). The conclusion in this study is that there is a relationship between knowledge and the incidence of acne vulgaris, there is no relationship between attitudes towards the incidence of acne vulgaris and there is no significant correlation between knowledge and attitudes of students.